Alkaline-Earth Metal Complexes: Mixed Ligand Complexes of Alkaline Earth Metal Salts of Some Organic Acids with Bis(8-hydroxy-5-quinolyl)-methane - Prakash, Dharam; Kumar Yadav, Ashok (Asian Journal of Chemistry, 2010)
Eight mixed ligand complexes of alkaline-earth metal salts of organic acids like 1-nitroso-2-naphthol (1N2N), o-nitrophenol (ONP), 2,4-dinitrophenol (DNP) and salicylaldehyde (Sal.H) with bis(8-hydroxy-5-quinolyl)-methane having the general formula [ML2]2H2L´, where M = Mg or Ca; L = deprotonated organic acids and H2L´ = bis(8-hydroxy-5-quinolyl)-methane, have been synthesized and characterized by elemental analysis and FTIR-spectral studies.